Ornaments of the metropolis : Siegfried Kracauer and modern urban culture - Reeh, Henrik (MIT Press, 2004)
"For Siegfried Kracauer the urban ornament was not just an aspect of design, it was the medium through which city dwellers interpreted the metropolis itself. In Ornaments of the Metropolis, Henrik Reeh traces variations on the theme of the ornament in Kracauer's writings on urbanism, from his early journalism in Germany between the wars to his "sociobiography" of Jacques Offenbach in Paris. Reeh argues that Kracauer's novel, essays, and historiography all suggest ways in which the subjective can reappropriate urban life. The book also includes a series of photographs by the author that reflect the ornamental experience of the metropolis in Paris, Frankfurt, and other cities."--Jacket